Value Co-creation Between the Service Systems of Trade Intermediaries, Customers, Partners and Finnish Cleantech SMEs Entering China - Gao, Cencen (My University, 2019)
Internationalization of small and medium-sized enterprises, SMEs, is an ongoing hot topic of economic and political discussion and debate in Finland. China, as the world leading economy in constant search for new high-end technology, has been considered as a potential new driver of Finnish SME internationalization growth. In particular, the cleantech industry has raised serious attention in the Chinese market, and Finnish SMEs have looked to tap into the market with the help of trade organization programmes. Also in Finland trade organizations have set forth various trade programmes, but the efficiency and effectiveness of those initiatives have not been studied intensively. The present study takes a holistic perspective on the value creation networks of the Finnish cleantech SMEs in China. In particular, the study seeks answers to how trade organizations can facilitate success at the market entry stage of the Finnish SMEs. Furthermore, the study takes a view of long term business success as the true measurement of the market entry’s success. The study presents a literature review on value co-creation, service systems, business models and SME internationalization and combines the key theoretical concepts into a theoretical framework. This framework concludes the key constructs of value co-creation networks, value sensing, configurational fit and business model development. The framework is then used as a structure for five separate case studies in which successful cleantech SME’s China market entries and trade organizations’ roles are analyzed. The data is analyzed in a cross-case analysis and ten key findings are concluded. These findings, at last, are presented in the light of the existing literature on SME internationalization in order to build a new platform for future research and discuss the generalizability of the case findings. The Chinese market is found to be large but highly competitive. It was found that trade organizations are well on the page on market entry stage support, but the focus should be aimed at boosting and accelerating SMEs internal strength and competence. It is concluded that the Chinese market is considered the world’s toughest, and the successful cases have typically improved its business operations holistically in order to meet the Chinese market needs. Last, a development structure for trade programme developers is presented.
Keywords: value co-creation, service science, SD logic, SME internationalisation, cleantech, China market entry, trade organisations